Pengaruh Pola Asuh Orang Tua terhadap Keterampilan Sosial Siswa - Nikki Tri Sakung; Nina Ikhwati Wahidah; Ana Fitriana (Jurnal Ilmiah Wahana Pendidikan, 2022)
The goal of education is to provide students with the social, emotional, and academic skills they will need to succeed in society in the future. Education is a cultural process that enhances human dignity. This study sought to ascertain how parenting affected children's social abilities. The approach utilized is a descriptive verification method that takes an ex post facto approach to the instrument. The study's findings thus indicate that, in the absence of a parenting style, a student's social skills are worth $12.394. The student's social skills will also improve by 0.532 percent for every one point gain in parenting. The results of the test suggest that parenting has an impact on children's social abilities. In this study, parenting trajectories include democratic parenting methods and permissive parenting trajectories. 20 students with an average social skills score of 70.5 have democratic parenting styles, while 10 students with an average social skills score of 63 have permissive parenting styles. The variation in scores demonstrates that parental practices have an impact on children's social abilities.